PERCEPATAN INOVASI LIMBAH COKLAT SEBAGAI PAKAN TERNAK KAMBING ETTAWA DI KECAMATAN TANJUNG BARU - Amrizal Anas; Ediset Ediset; Rahma Yanti (Jurnal Peternakan, 2017)
ABSTRACTThis research aims to determine: a) the acceleration of innovation adoption cocoa waste as animal feed of Ettawa Cross Breed in the district of Tanjung Baru Tanah Datar, b) problems encountered in the implementation of the waste cocoa breeders as animal feed of Ettawa Cross Breed in the district of Tanjung Baru Tanah Datar. This research used survey, where respondents in the sample in this research is the goat breeders in the district of Tanjung Baru as many as 30 people. The data collected are primary data with the aid of questionnaires and secondary data with study of literature and related agencies. The results of this research indicate that the size of the adoption of the innovation seen on the velocity or the time interval between the receipt of the information and the application is done in the district of Tanjung Baru classified as fast (less than 1 week) 66.67%, broad application of innovation or the proportion of the number of animals that have been given the new innovations in the district of Tanjung Baru is applied by 76.67%, and intensification quality by comparing with recommended application submitted by extension in the district of Tanjung Baru is good at 73.33%.